Strengthening collaboration through collective impact: A rural Australian case study. Issue 4 (8th August 2021) - Williams, Tara; Lakhani, Ali; Spelten, Evelien
ABSTRACT: Increasing health inequalities and entrenched social problems demands systemic change that challenges the status quo of current programs and policies and enhances intersectorial collaboration between government, service providers, and communities. Collective Impact (CI) is one approach aimed to support local communities solve complex and systemic problems. A case study design is used to describe a rural Australian community's approach to strengthening collaboration in an early stage CI. Data included in-depth interviews (N = 11), that were thematically analyzed to develop descriptive themes. Barriers to successful collaboration were complexity of change, system dynamics and a lack of community engagement. Successful collaboration was facilitated by inclusive and diverse relationships; innovation and adaption and a willingness to disrupt the system. Findings suggest that CI offers a promising approach to strengthening collaboration and understand how multiple and diverse partners work together in adaptive and emergent ways to bring about community-level change.